Application of oil and fat industrial wastes for modification of the fillers - Chobit, M. R.; Vasylyev, V. P.; Panchenko, Yu. V. (Видавництво Львівської політехніки, 2017)
After the execution of this work were derived polymer composite materials (PCM) based on polystyrene and PVC. In the course of this work were obtained with PCMmodified and unmodified fillers: chalk, kaolin, aerosil, titanium dioxide, aluminum oxide. It kinetics modifications fat-containing waste mineral fillers of "Novovolyns`ky oil and fat factory", thermomechanical properties, tensile strength and toughness obtained of PCM. The synthesized composites can be used in various industries, such as engineering, aviation, production of packagingmaterials andmore
Keywords: polymer composites; polystyrene; polyvinyl chloride; modified mineral filler